Reimagining Character Education in Islamic Schools Through Prophetic Values and Digital Citizenship Competencies Integration - Faruk Kerem Sentürk; Esraa Al-Sarray; Farouq Ahmad Faleh Alazzam (Al Husna: Jurnal Ilmiah Pendidikan Agama Islam, 2024)
The rapid expansion of digital technologies has significantly transformed educational environments, creating new opportunities and challenges for character education in Islamic schools. While digital platforms facilitate learning accessibility, communication, and knowledge sharing, they also expose students to ethical risks such as cyberbullying, misinformation, digital addiction, privacy violations, and declining moral sensitivity. Consequently, Islamic educational institutions are required to redesign character education frameworks that respond effectively to contemporary digital realities while preserving religious and moral values. This study aims to explore the integration of Prophetic Values and Digital Citizenship Competencies as a comprehensive framework for reimagining character education in Islamic schools. Employing a qualitative library research approach concerning Islamic character education, prophetic pedagogy, digital citizenship, educational ethics, and school transformation. The findings indicate that prophetic values, including ṣidq (truthfulness), amānah (trustworthiness), tablīgh (communicative responsibility), and faṭānah (wisdom), provide strong ethical foundations for developing responsible digital citizens. Furthermore, integrating digital citizenship competencies with Islamic moral education enhances students’ ethical awareness, critical thinking, digital responsibility, social participation, and online behavior. The novelty of this study lies in proposing an integrative conceptual framework that systematically connects prophetic educational values with contemporary digital citizenship competencies to support holistic character development in Islamic schools. The study concludes that sustainable character education in the digital age requires a balanced integration of religious ethics, technological literacy, and responsible citizenship practices